Upaya dan Hambatan dalam Penanggulangan Kejahatan Pembuangan Bayi di Kabupaten Manggarai - Petronela Yelita Engkot; Karolus Kopong Medan; Debi F. Ng. Fallo (International Forum of Researchers and Lecturers, 2024)
The purpose of this research is to analyze the efforts and obstacles in overcoming the crime of baby dumping in Manggarai Regency. This research is empirical research, which is research conducted directly in the field and carried out at the Manggarai Resort Police and the Office of Women's Empowerment and Child Protection (DP3A) of Manggarai Regency. Data collection techniques used interviews and document/literature studies. The data used were primary and secondary data. The results of the data processing were analyzed descriptively qualitative. The results of this study show that: (1) The efforts made by the Manggarai Resort Police and DP3A of Manggarai Regency in overcoming the crime of baby dumping are Repressive and Preventive efforts. (2) The inhibiting factors in the efforts to overcome the crime of baby dumping in Manggarai Regency are the difficulty in identifying the perpetrators of baby dumping, limited human resources, facilities and infrastructure, agencies that do not carry out their duties properly, community conditions.